Work-family conflict categories and support strategies for married female nurses: a latent profile analysis - Xin Yao; Siqi Wen; Ziling Song; Jing Wang; Yuanyuan Shen; Xiaoqiong Huang (Frontiers Media S.A., 2024)
ObjectiveTo clarify subgroups of married female nurses experiencing work-family conflict (WFC), explore the factors associated with the subgroups, and determine how desired support strategies differ among the subgroups.MethodsData was collected from a sample of 646 married female nurses from public hospitals in Zhejiang Province, China, in December 2021. Latent profile analysis was used to group the participants, and multiple logistic regression was used to identify factors associated with higher WFC. The STROBE criteria were used to report results.ResultsAccording to latent profile analysis, there were three distinct profiles of WFC among married female nurses: "low-conflict type," "work-dominant-conflict type," and "high-conflict type." These profiles differed in the number of children, night shifts, family economic burden, childcare during working hours, family harmony, colleague support, and nurse-patient relationships. Nurses with multiple children, higher pressures in childcare during working hours, heavier family economic burdens, lower family harmony, lower colleague support, and poorer nurse-patient relationships are more likely to be classified as "high-conflict type" nurses.ConclusionThis study found that married female nurses experience different types of WFCs. The structure of these WFCs and their associated factors suggests that customized intervention strategies can be developed to address the specific needs of married female nurses.